Theoretical and Experimental Aspects of Syntax-Discourse Interface in Heritage Grammars - Ivanova-Sullivan, Tanya (Empirical Approaches to Linguistic Theory, 2014)
InTheoretical and Experimental Aspects of Syntax-Discourse Interface in Heritage Grammars,Tanya Ivanova-Sullivan investigates comprehension and production of anaphoric dependencies in heritage Russian. She explains the representational and processing mechanisms behind the divergent behaviour of the experimental group.